Identification and sequence analysis of two regulatory genes involved in anaerobic toluene metabolism by strain T1. - Coschigano, P W (1997)
T1 is a denitrifying bacterium isolated for its ability to grow with toluene serving as the sole carbon source. Mutants of this strain that have defects in the toluene utilization pathway have been isolated and have been separated into classes based on growth phenotypes. A cosmid clone has been isolated by complementing the tutB16 (for toluene utilization) mutation. The complementing gene has been localized to a 3.3-kb DNA fragment. An additional open reading frame upstream of the tutB gene has also been identified and is designated tutC. The nucleotide sequence and the predicted amino acid translation of the 6.4-kb DNA fragment that contains these genes are presented. The tutB and tutC gene products of strain T1 have homology to members of the two-component sensor-regulator family and are proposed to play a role in the regulation of toluene metabolic genes of strain T1. To our knowledge, this is the first published report of the isolation of mutants defective in anaerobic aromatic hydrocarbon degradation. Additionally, we report for the first time the cloning of genes involved in an anaerobic aromatic hydrocarbon degradation pathway.